Websites of Central Universities in India: A Webometric Analysis - Babu, B. Ramesh; Jeyshankar, R.; Nageswara Rao, P. (DESIDOC Journal of Library & Information Technology, 2010)
Webometrics is concerned with measuring aspects of the web: websites, web pages, parts of web pages, words in web pages, etc. This study examines 40 central universities websites in India. Investigates domain systems of the websites, analyses the number of webpages and link pages and calculates the simple web impact factor, self link web impact factor, external link web impact factor and revised web impact factor for Central universities in India and ranks the websites as per the WIF. It also develops a novel network diagram showing link structures between web nodes in webometric analysis. This study warns against taking the analogy between citation analysis and link analysis too far. DOI: 10.14429/djlit.30.458